Decidual prolactin in the first quarter of normal pregnancies and complicated with severe preeclampsia. - Paredes Villanueva, Fredy (2015)
Amniotic fluid or decidual prolactin (PRL) levels PRL were assessed in 48 normal pregnant women and 48 severe preeclamptic women at 27 to 42 weeks gestation. Amniotic fluid specimens were obtained by periumbilical amniocentesis and PRL measurements were determined by homologous radioinmunoassay (RIA). At 2730 weeks of pregnancy, decidual PRL levels were 2 845 ± 439 mUl/L in normal pregnancies and 3 124 ± 504 mUVL in severe preeclamptic patients (P < 0,05). At 3134 weeks of gestation, decidual PRL levels were 2383 ± 77 mUl/L and 2 654 ± 379 mUl/L, respectively (P < 0,05). At 3538 weeks of pregnancy, PRL values were 2 420 ± 144 mUl/L and 2 616 ± 178 mUVL, respectively (P > 0,05). Between 3942 weeks pregnancy, PRL measurements were 2354 ± 82 mUI/L and 2399 ± 95 mUI/L, respectively (P > 0,05). In normal pregnancies there was a mild negative correlation between decidual PRL levels and gestational age during third trimester, without statistical significance (r = 0,20; P > 0,05). However, there was a high negative correlation in pregnancies complicated with severe preeclampsia (r= 0,770; P<0,05). Present data suggest: 1) Decidual PRL levels in normal pregnancies are lower than those of pregnancies complicated with severe preeclampsia at 2734 weeks of gestation; but globally, there is no significant difference during the third trimester. 2) Decidual PRIL levels follow a relative plateau pattern during the third trimester of normal pregnancies, with decreasing pattern in preeclamptic patients, 3) Amniotic fluid PRL shows lower levels in normal pregnancies than in pregnancies complicated with severe preeclampsia and less variability than previously reported.